LAZ SIDOGIRI AND SOCIAL TRANSFORMATION TOWARDS ECONOMIC EMPOWERMENT OF BANYUWANGI COMMUNITY BASED ON ISLAMIC VALUES - M Sufyan Fathoni; Joharul Fathoni (Program Studi Ekonomi Syariah, Universitas Pangeran Diponegoro Nganjuk, 2025)
This study aims to analyze the strategies employed by the Sidogiri Zakat Institution (LAZ) in integrating Islamic values within its community economic empowerment programs and to assess the impact of these strategies on social transformation. Utilizing a descriptive qualitative approach, data were gathered through interviews, observations, and document analysis. The findings reveal that LAZ Sidogiri applies both consumptive and productive distribution models, supported by a variety of programs focused on education, healthcare, environment, economy, and needs-based social assistance. Despite the structured nature of these initiatives, several challenges persist, including limited professional human resources, weak monitoring mechanisms, and negative public perceptions. The positive outcomes of the programs include increased access to capital and entrepreneurship training, albeit with a limited reach. This study concludes that enhancing public engagement strategies, improving human resource quality, and ensuring institutional transparency are crucial for broadening program impact and sustaining social transformation based on Islamic principles.